Alternative route to a hypoglossal canal dural arteriovenous fistula in case of failed jugular vein approach. Issue 2 (April 2021) - Dahl, Rasmus Holmboe; Biondi, Alessandra; Caterino, Fortunato Di; Vitale, Giovanni; Poulsgaard, Lars; Benndorf, Goetz
Hypoglossal canal dural arteriovenous fistulas (HC-DAVF) involve the anterior condylar vein (ACV) and anterior condylar confluence (ACC). They often present with tinnitus, bruit, and hypoglossal nerve palsy. The most common treatment in HC-DAVFs is transvenous embolization using coils and the most direct transvenous route is the trans-internal jugular vein access. When this approach is not feasible, a treatment attempt is possible through alternative routes. We report 2 patients with DAVFs involving the anterior condylar confluence. The first patient presented with pulsatile tinnitus and hypoglossal nerve palsy, and was treated by a standard transjugular approach. The second patient presented with pulse-synchronous bruit. Following an unsuccessful attempt of the transjugular approach, the fistulous point was reached via the deep cervical vein and complete occlusion was achieved by coil deployment. Both patients had complete regression of symptoms. Endovascular therapy is the elective treatment for HC-DAVFs and the transjugular approach is the most commonly used. The deep cervical vein (DCV) can be an alternative transvenous route when the transjugular approach fails.